2014
DOI: 10.1007/s00701-014-2206-6
|View full text |Cite
|
Sign up to set email alerts
|

Posterior auricular artery as an alternative donor vessel for extracranial-intracranial bypass surgery

Abstract: The PAA is a rarely described as an appropriate donor vessel for an EC-IC bypass. Its prevalence is 5.7% and it can successfully be used as an alternative donor vessel. The awareness among cerebrovascular surgeons about the presence of a PAA and knowledge about its anatomy may be valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…However, four of the five Type D cases had equivalent size to the STA, and one was obviously larger than STA. Following our case report, three more similar case reports were published [ 13 ]. A series of consecutive 175 patients who received bypass surgery found that 5.7% of patients had PAAs large enough for use as a donor artery for revascularization surgery, which corresponds to Type D [ 13 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, four of the five Type D cases had equivalent size to the STA, and one was obviously larger than STA. Following our case report, three more similar case reports were published [ 13 ]. A series of consecutive 175 patients who received bypass surgery found that 5.7% of patients had PAAs large enough for use as a donor artery for revascularization surgery, which corresponds to Type D [ 13 ].…”
Section: Discussionmentioning
confidence: 56%
“…Following our case report, three more similar case reports were published [ 13 ]. A series of consecutive 175 patients who received bypass surgery found that 5.7% of patients had PAAs large enough for use as a donor artery for revascularization surgery, which corresponds to Type D [ 13 ]. This five-fold difference from the present finding of 1.2% might be the result of selection bias, as all patients underwent bypass surgery.…”
Section: Discussionmentioning
confidence: 56%
“…Most of the time, the PAA originates from the external carotid artery just superior to the occipital artery and runs toward the stylomastoid foramen. At the stylomastoid foramen, the PAA courses between the mastoid tip and auricle, running almost vertically towards its vertex 7.5 cm from the mastoid tip . It is well known that the PAA always accompanies the PAN.…”
Section: Introductionmentioning
confidence: 99%
“…At the stylomastoid foramen, the PAA courses between the mastoid tip and auricle, running almost vertically towards its vertex 7.5 cm from the mastoid tip. 20 It is well known that the PAA always accompanies the PAN. In addition, when compared to the PAN, the PAA has a larger diameter, is pulsatile, and has distinguishing color characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the carotid arteries in relation to their diameters and level of bifurcation varied widely in literature 1 – 5 . The importance of the carotid arteries is based on their distribution territories for face, mouth, eye, nose, brain, on associated pathologies as the atheromatosis and on new diagnostic techniques and interventional approaches 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%